PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION MELALUI KEPUASAN KERJA PADA KARYAWAN PT. ADIRA QUANTUM MULTIFINANCE CABANG PEKANBARU - Zaki, Hammam; Marzolina, Marzolina (Jurnal Tepak Manajemen Bisnis, 2016)
The purpose of this study was to determine the effect of workload andcompensation for job satisfaction and turnover intention of employees at PT. AdiraQuantum Multifianance Pekanbaru branch. The research sample as many as 157people were selected using census method that is the entire population being sampled,while data collected using questionnaires and analysis techniques used are two-stageregression analysis using SPSS version 22.The results showed that the workloadsignificantly affect job satisfaction, and compensation have a significant impact on jobsatisfaction, workload and compensation simultaneously significant effect on jobsatisfaction and job satisfaction significantly influence employee turnover intention. Theresults of this study is, any increase job satisfaction hence potentially lower workload,and high compensation potential to increase job satisfaction. Increased job satisfactionhas the potential to reduce the rate of employee turnover intention.